Hubungan Kepatuhan Minum Obat dan Gaya Hidup terhadap Kestabilan Tekanan Darah pada Pasien Hipertensi di Rumah Sakit Permata Medika Semarang - Amalia Safinatun Naja; Maulidta Karunianingtyas W (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Hypertension is a health problem that can increase the risk of cardiovascular disease and other complications. Hypertension is often referred to as a silent killer because it often doesn't cause obvious symptoms until complications develop. Hypertension can be controlled through pharmacological therapy with medication adherence and non-pharmacological therapy through adopting a healthy lifestyle. However, many patients do not optimally implement these measures, resulting in unstable blood pressure. This study aims to determine the relationship between medication adherence and lifestyle and blood pressure stability in hypertensive patients at Permata Medika Hospital, Semarang. This study used a quantitative method with a cross-sectional design on 79 outpatients with hypertension selected using a purposive sampling technique. Data were collected using the MMAS-8 questionnaire, a lifestyle questionnaire, and blood pressure measurements, then analyzed using the Spearman Rank test. The results of the study showed a significant relationship between medication adherence and blood pressure stability (p = 0.001; r = 0.842) and between lifestyle and blood pressure stability (p = 0.001; r = 1.000). This indicates that the more patient adherence to medication and the better lifestyle they adopt, the more stable their blood pressure. There is a significant relationship between medication adherence and lifestyle on blood pressure stability in hypertensive patients at Permata Medika Hospital Semarang.